Türk hukukunda hekimlik sözleşmesi - İpekyüz, Filiz Yavuz (My University, 2003)
İnsanın varlığını sürdürmesinde ve geliştirmesinde sağlıklı yaşam hakkı büyük önem taşır. Hekim ile hasta arasındaki ilişkide karşımıza bir ödev-hak ekseni çıkar. Bu eksende ideal bir etik ilişki, ödev ve hakların karşılıklı denge ve eşitlik halinde olmasını gerektirir. İnsan hakları ve yeni sosyal hak kavramları alanındaki gelişmelere bağlı olarak, günümüzde hekim sorumluluğunun yanı sıra hasta hakları da yasal düzenlemelerle tespit edilmiştir. Türk hukukunda hekimlik sözleşmesini konu alan bu çalışmanın amacı hekim ile hasta arasındaki ilişkinin hukuki niteliğini, tarafların karşılıklı hak ve borçlarını, borçların ihlalinden doğan sorumlulukları, zararların hukuki düzeyde tazmin yollarını ve hasta-hekim ilişkisinin hangi hallerde sona erdiğini belirlemektir. Konuyu incelerken borçlar hukuku sözleşme esaslarının yanı sıra meslekle ilgili mevzuat temel alınmıştır. Çalışma serbest veya özel bir kuruma/ kuruluşa bağlı olarak çalışan hekimleri kapsamaktadır; çünkü kamu kuruluşlarında çalışan hekimler açısından kamu hukukuna giren bir ilişki söz konusudur ve sorumluluk öncelikle kuruluş idaresindedir. Bu çalışmayla ortaya konmak istenen başlıca sonuçlar kişilik hakkı kavramının hekimlik sözleşmesindeki önemi, bu kavrama dahil olan hasta haklarını açıklığa kavuşturacak yaklaşımlar, insanın beden ve ruh sağlığı açısından hekimlik mesleğinin sorumluluğunu düzenleyecek bir çerçevedir. MEDICAL CONTRACT IN TURKISH LAW

The survival and improvement of human existence is very important for the right of healthy life. In the relationship between physician and patient, we come across a duty-right axis. An ideal ethical affiliation in this axis requires a mutual balance and equality between duties and rights. As a result of the developments in the realm of human rights and new social right concepts, medical responsibility and patient rights have been set up by legal regulations. The purpose of this study, dealing with medical contract in the Turkish law, is to establish the legal character of the relationship between physician and patient, the mutual rights and liabilities, the responsibilities due to the violations, the ways of legal indemnity of the damages and the termination of the relationship. The inquiry into this subject is based on the essential contract rules in the law of obligation as well as the professional regulations. The study covers only the medical practitioners working independently or in the private institutions/ establishments, because the medical relationship in the public establishments is related with public law and the responsibility primarily belongs to the administration. The conclusions to be achieved by this study are the significance of the personality right in the medical contract, the approaches clarifying the patient rights incorporated in this concept and a framework regulating the responsibility of the medical profession in relation to the physical and spiritual health of human being.
Keywords: Özel Hukuk; Private Law